State-business dynamics and its impact on high-tech industrial policy outcomes - Shazly Zain (2019)
The prevailing narrative is that advanced economies are similar, being service-oriented and having a reduced manufacturing sector. Manufacturing sectors in advanced economies are also thought to be very high-tech in nature. However, the author finds that a select group of advanced economies still have significant manufacturing sectors. Within these economies, the levels of high-tech manufactured goods vary widely. This dissertation attempts to expand current industrial policy literature and understand the mechanisms enabling the variation in high-tech manufacturing output by considering the relationship between the state and businesses in developing high-tech manufacturing systems. The author utilizes the framework of statism and corporatism to measure the influence of the state and businesses in the state-business dynamics. The author finds that economies with high levels of corporatism or have high degrees of statism to substitute the network externalities of corporatism have higher levels of high-tech manufacturing output.